Smart feeding for improved performances and meat and milk quality of small ruminants - Valenti B.; Ben Salem H. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The drylands are home to large flocks of sheep and goats but do not produce sufficient feedstuffs to overcome the nutritional requirements of livestock. This situation is exacerbated by the impacts of climate change, in particular through the quantitative and qualitative decrease contribution of forage and range vegetation to the diets of these animals. Therefore, the production cost is continuously increasing and the sustainability of livestock production systems is threatened. Producing more with minimum inputs has become a challenge for livestock breeders. Some affordable feeding technologies and practices hold promise to tackling such objective. For example, infrequent nitrogen supplementation did not compromise livestock performance and maximized cost efficiency. Some locally produced feed resources had been efficient in replacing common and expensive feed sources, mainly concentrate feeds in sheep and goat diets. Appropriate watering is a prerequisite to optimize feeding efficiency. Natural additives phytochemicals are investigated as potential substitutes to enhance livestock production. This is mainly referring to plants, plant extracts and or natural plant compounds (e.g. tannins, saponins, essential oils, etc.). These alternative feeding options had increased feeding efficiency, production performance and or meat and milk quality. A range of plants are a valuable source of phytochemicals such as vitamins, polyphenols, minerals, fibre, unsaturated fats that show antioxidant, antimicrobial, anticholesterolemic and other positive biological activities in humans. It has been estimated that 30% of the plant material processed by the food industry is discarded as non-human edible waste. In a global context characterized by a growing pressure for increasing the sustainability of production systems, including agro-industrial by-products (AIBP) in the diet of farm animals represents a strategy to mitigate the environmental impact of livestock production, especially for ruminants. In particular, the dietary administration of AIBP to replace feeds traditionally included in the animal feeding such as, cereals and pulses, could reduce the competition between feed and food. Moreover, during the last years, research showed that the inclusion of AIBP and some plants containing secondary compounds in the ruminant diet may have positive effects on animal health and can improve the nutritive value and the shelf-life of milk and meat. However, discontinuous availability during the year, unbalanced chemical composition and the presence of antinutritional factors represent critical issues that need to be evaluated to effectively exploit these novel feeds. This review presents and discusses the recent findings on smart feeding as cost-effective and environment friendly option to reiterate the importance of livestock breeding in production systems that are exposed to climate change.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)